2020
DOI: 10.1177/1460458219894094
|View full text |Cite
|
Sign up to set email alerts
|

Telemonitoring readiness among Austrian diabetic patients: A cross-sectional validation study

Abstract: Digitalized healthcare services offer remote and cost-effective treatment of diabetes patients. Thus, the present online study analyzed the readiness to use telemonitoring among Austrian diabetes patients. We developed and validated a German version of the patient telehealth readiness assessment tool and performed quantitative context analysis of free-text comments on perceived barriers and benefits of telemonitoring. Participants (n = 41, 42.6% females) achieved a medium average readiness level for telemonito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 34 publications
(61 reference statements)
1
24
0
Order By: Relevance
“…As we conducted an online exploratory study, we abstained from sample size calculation and did not use advanced recruiting strategies and incentives for participation, which could clearly increase response rates in follow-up studies [22]. Nevertheless, similar sample sizes are also reported in related studies [8,18,20,42]. As expected, the age of parents correlated with the age of the children.…”
Section: Limitationsmentioning
confidence: 91%
See 2 more Smart Citations
“…As we conducted an online exploratory study, we abstained from sample size calculation and did not use advanced recruiting strategies and incentives for participation, which could clearly increase response rates in follow-up studies [22]. Nevertheless, similar sample sizes are also reported in related studies [8,18,20,42]. As expected, the age of parents correlated with the age of the children.…”
Section: Limitationsmentioning
confidence: 91%
“…We conducted a Web-based questionnaire study among a cross-section of the Austrian population. We developed a German study questionnaire based on previous surveys and details are reported elsewhere [ 1 , 10 , 18 , 19 , 20 ]. The online survey was enabled by the Web-based survey tool SoSci Survey and was accessible barrier-free from 28 February to 14 June 2018 [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we conducted an online study, we did not use incentives for participation, which could clearly increase response rates in follow-up studies. Although similar sample sizes are reported in related studies, the response rate was low, potentially mirroring the fact that health professionals are commonly considered as a hard to reach population, and [ 18 , 19 , 33 , 49 , 50 , 51 ]. Notably, we abstained from reporting results of inferential statistics, as, potentially due to the small sample size in the respective subgroups, age, gender, and specialization did not differ regarding the telehealth readiness score (data not shown).…”
Section: Limitationsmentioning
confidence: 66%
“…A further part of the survey contained the commonly used practitioner telehealth readiness assessment tool (PRAT) in German validated in prior research [ 18 , 21 , 30 , 31 , 32 , 33 ]. The PRAT is a scale of 17 items using a 5-point Likert scale ranging from disagree = 1 to agree = 5 to assess a broad range of aspects of readiness for telehealth.…”
Section: Methodsmentioning
confidence: 99%